(untitled) (Swiss Medical Weekly, 2016)
BACKGROUND: Concerns regarding the use of direct oral anticoagulants (DOACs: apixaban, dabigatran, edoxaban, rivaroxaban) in the elderly persist owing to the lack of randomised controlled trials targeting this age group. OBJECTIVES: The aim of this study was to assess the efficacy and safety of DOACs in elderly patients (aged 75 years or more) with atrial fibrillation or venous thromboembolism (VTE), based on already published large randomised trials. METHODS: EMBASE, MEDLINE and the Cochrane Library were searched from inception to June 2015 for phase III trials. Pooled odds ratios with 95% confidence intervals were calculated for the target population using the fixed effect model. Heterogeneity between trials was assessed using the I2 Higgins test. RESULTS: A total of 30 655 participants aged 75 or older from eight studies (two apixaban, one dabigatran, two edoxaban, three rivaroxaban) were included in the statistical evaluation. Pooled analysis revealed that treatment with a DOAC was associated with a statistically significant odds reduction for stroke and embolism in elderly patients with atrial fibrillation. Also, DOACs significantly reduced the number of recurrent VTE events or VTE-related deaths in the participants aged 75 years or more with VTE. There was no statistically significant difference in safety outcome for both indications with DOAC compared with vitamin K antagonists although some differences in safety profiles between the DOACs were apparent. CONCLUSION: DOACs show the same or greater efficacy than vitamin K antagonists in elderly patients with atrial fibrillation and VTE. Individual differences between DOACs in terms of safety profile cannot be excluded on the basis of current evidence. Direct head-to-head comparisons are needed to investigate possible divergence in pharmacological profiles between DOACs. Additionally, further studies conducted in real-word settings and in the frail elderly are ongoing and it would be interesting to target this particular patient group.